The critique of modernity from the Huarochirí Manuscripts - Hernández Soto, Javier Eduardo (2021)
We propose a critique of modernity from the Andean myths, especially those of the Huarochirí Manuscripts. To carry out this task we approach the work of Franz Hinkelammert, highlighting above all his study of modern reason, and how it generates new myths to cover up, justifying exploitation and world domination. In dialogue with this philosopher we want to show the possibility of critically thinking about modernity from another horizon, that of Andean culture, since at the same time that modern myths arise, he also elaborates critical myths of modernity, which can be claimed as part of a broad movement of resistance.